KEBUTUHAN ENERGI UNTUK MEMPROSES (INGOT-WAFER SEL- MODUL) KRISTAL SILIKON DAN WAKTU PENGEMBALIAN DALAM PEMANFAATAN PENERANGAN RUMAH TANGGA FOTOVOLTAIK, SOLAR HOME SYSTEM - Abubakar Lubis (Jurnal Teknologi Lingkungan, 2008)
This paper is to review existing knowledge on energy requirements for manufacturing photovoltaic (PV) module and system. Estimate energy (primary energy) requirements for manufacturing PV module for scenario: Low* and High1. For multi crystalline silicon (mc-Si)a. Low is 4200 MJ/ m2 (mc-Si) or 35 MJ/Wp = 3,395 kwh/Wpb. High is 11600 MJ/ m2 (mc-Si) or 96 MJ/Wp = 9.312 kwh/Wp2. For a single –crystalline (sc-S)a. Low is 6000 MJ/ m2 or 47 MJ/Wp = 4,559 kwh/Wp.b. High is 13900 MJ/ m2 or 109 MJ/Wp = 10.573 kwh/WpEstimate energy production (final yield) for application SHS (50 Wp) multi – crystalline (mc-S) is 65 kwh/Wp/year (1 Wp produce 1,3 kwh/year. Estimate Energy Pay-back Time ,” take energy to save energy”. for Solar Home System Application for over 20 year system life (under 1900 kwh/ m2/year irradiation) are 3-4 years for low scenario and 8 years for high.